ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH AKUISISI - Dewi, Putu Yulia Kumalasari; Suryantini, Ni Putu Santi (E-Jurnal Manajemen, 2018)
Financial performance is a reflection of the financial condition of a company. The purpose of this study is to determine the significance of differences in corporate financial performance before and after the acquisition of mining acquisition companies in the BEI period 2011-2013 by analyzing financial performance one year before and one year after acquisition. The method of determining the sample is the census that the entire population is used as a sample which is obtained by 5 acquirer companies. The analysis technique used is paired t-test (Pair-Sample T-test). Based on the results of the analysis found that financial performance measured by five financial ratios of CR, ROA, DER, TATO, PER that did not differ significantly after acquisition compared to before acquisition. The acquisition strategy has not been fully achieved due to the condition of financial performance after the acquisition has not increased. The motive of the acquisition is not economic but non-economic. The acquirer company which to achieve success, must make preparations by looking at the conditions of the company to be taken over.